Ultrafine Magnetic Particles: A DIET-Proxy in Organic Rich Sediments? - Ustra, Andrea Teixeira; Mendonça, Carlos; Leite, Aruã da Silva; Macouin, Melina; Doherty, Rory; Respaud, Marc; Tocuti, Giovana (Frontiers in Earth Science, 2021)
In this work we present results of the magnetic properties characterization of sediment samples from a brownfield site that is generating methane biogas in São Paulo – Brazil. We applied interpretation procedures (frequency dependent susceptibility and magnetization decay) appropriate to study the ultrafine magnetic fraction response of the samples. The distribution of superparamagnetic particles correlates well with the detected methanogens, suggesting that the microbial activity producing methane generates these ultrafine particles, different from the magnetic particles at other depth levels. We propose the use of two simple measurement and interpretation techniques to identify superparamagnetic fingerprints. The results presented here support the use of environmental magnetism techniques to investigate biogeochemical processes of anaerobic microbial activity.